Morbidity from malaria in children in the year after they had received intermittent preventive treatment of malaria: a randomised trial. - Amadou T Konaté; Jean Baptiste Yaro; Amidou Z Ouédraogo; Amidou Diarra; Adama Gansané; Issiaka Soulama; David T Kangoyé; Youssouf Kaboré; Espérance Ouédraogo; Alphonse Ouédraogo; Alfred B Tiono; Issa N Ouédraogo; et al. (PLoS ONE)
Background Interventions that reduce exposure to malaria infection may lead to delayed malaria morbidity and mortality. We investigated whether intermittent preventive treatment of malaria in children (IPTc) was associated with an increase in the incidence of malaria after cessation of the intervention. Methods An individually randomised, trial of IPTc, comparing three courses of sulphadoxine pyrimethamine (SP) plus amodiaquine (AQ) with placebos was implemented in children aged 3-59 months during the 2008 malaria transmission season in Burkina Faso. All children in the trial were given a long lasting insecticide treated net; 1509 children received SP+AQ and 1505 received placebos. Passive surveillance for malaria was maintained until the end of the subsequent malaria transmission season in 2009, and active surveillance for malaria infection, anaemia and malnutrition was conducted. Results On thousand, four hundred and sixteen children (93.8%) and 1399 children (93.0%) initially enrolled in the intervention and control arms of the trial respectively were followed during the 2009 malaria transmission season. During the period July 2009 to November 2009, incidence rates of clinical malaria were 3.84 (95%CI; 3.67-4.02) and 3.45 (95%CI; 3.29-3.62) episodes per child during the follow up period in children who had previously received IPT or placebos, indicating a small increase in risk for children in the former intervention arm (IRR = 1.12; 95%CI 1.04-1.20) (P = 0.003). Children who had received SP+AQ had a lower prevalence of malaria infection (adjusted PR: 0.88 95%CI: 0.79-0.98) (P = 0.04) but they had a higher parasite density (P = 0.001) if they were infected. There was no evidence that the risks of moderately severe anaemia (Hb<8 g/dL), wasting, stunting, or of being underweight in children differed between treatment arms. Conclusion IPT with SP+AQ was associated with a small increase in the incidence of clinical malaria in the subsequent malaria transmission season. Trial registration ClinicalTrials.gov NCT00738946.